ANALISA SISTEM JAM TERBANG PADA PENERBANG - Peniarsih Peniarsih (JURNAL TEKNOLOGI INDUSTRI, 2015)
Some airlines even menisyaratkan "flying hours" as one measure in determining the "salary" an aviator, moreover, these flying hours will determine an aviator to appropriately referred to as "aviator senior" or "junior pilot". Further than that, the general questions that often take precedence in the event of a plane crash, then that is often asked by the public is what the name of his plane, his aviator whom and for how long the pilot had flying hours?Flying hours will generally be associated with prolonged or sebentarnya a pilot flying an airplane, the more often an aviator have the flying hours flying hours will be higher. In contrast, if a pilot flying the aircraft rarely then flying hours will be low. Ability and greatness of an aviator, his public will be determined by how long he has flight hours. The higher the flying hours, then the public against an aviator award will certainly be higher than for a new pilot dozens of hours just fly the plane. Keywords: Clock Fly, Airmen, Fly Clock Systems